“What’s the Problem Represented to be” in Lund Municipality's district program for Norra Fäladen - Mata Alvarez,Samaria (2026)
This analytical essay critically examines how social sustainability is constructed within Lund’s municipality district development program for Norra Fäladen. The existing research widely acknowledges that sustainable development and social sustainability are characterized by conceptual ambiguity and a lack of consensus regarding definition and measurement. Despite this, they are leading concepts for international and local development policies. Through a governmentality perspective this study conceptualizes policies and programs as governance practices aiming to regulate the conduct of the population in line with specific political objectives. By employing the post-structuralist analysis method “What is the Problem Represented to be?” (WPR) to examine how social sustainability is problematized in the district development program for Norra Fäladen. This essay's intent is to contribute to a broader understanding of how public administration governs through the use of abstract concepts. This study concludes that social sustainability is constructed as a desirable outcome of the district’s development, while the means to achieve it are predominantly framed in terms of physical planning, urban design, and spatial transformation. As a result, complex social challenges are rendered governable primarily through interventions in the built environment.
Keywords: Governmentality; WPR; social hållbarhet; Norra Fäladen; Lunds kommun.